2016
DOI: 10.3311/ppci.9243
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table test and time-history analysis of high-rise diagrid tube structure

Abstract: IntroductionWest tower in Guangzhou Zhujiang new city is a new type of tube structure system as shown in Fig. 1 and Fig. 2, which has total floor area of 247000 square meters. Outer tube of this structure consists of diagonal members which are concretefilled steel tube columns, while inner tube consists of shear walls and steel frames. Shear walls of inner tube are cancelled above 67th floor and replaced by steel frames. Elevation for the underground fourth floors is -18.7meters, and elevation for the top of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The test model was a single room of the entire building on a full scale, that is, it can be used as a real house for living. Because of the use of the full-scale housing model, according to similarity ratio theory (Liu et al, 2017; Zhou and Lv, 2012), the similarity ratio of the shaking table test is 1.…”
Section: Design Of the Integrated Housementioning
confidence: 99%
“…The test model was a single room of the entire building on a full scale, that is, it can be used as a real house for living. Because of the use of the full-scale housing model, according to similarity ratio theory (Liu et al, 2017; Zhou and Lv, 2012), the similarity ratio of the shaking table test is 1.…”
Section: Design Of the Integrated Housementioning
confidence: 99%
“…As a new type of high‐rise building structure, diagrid tube structure subjects to complex loading. [ 27,28 ] Under normal operational condition, inclined column component section not only bears internal force mainly based on axial force, but also bends moment and shear force, and so forth, which makes the stress of structure component section become complicated, and many uncertain factors of component failure appear. [ 29 ] Therefore, it is necessary to study the damage sequence of components, the vulnerability extent of components, and the robustness of structures under vertical loads.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [14] performed experimental and FE studied on the static behavior of double-skin CHS X-joints under axial compression, and proposed the corresponding design equations for the double-skin X-joints. Nassiraei et al [15] performed FE analyzed to study the effects of doubler plate size and connections geometry on the ultimate strength, initial stiffness, and failure modes in CHS T-and Y-joints reinforced with doubler plate subjected axially tensile load [16]; and the results indicated that the doubler plate can significantly increase the initial stiffness, ultimate capacity, and considerably improve failure modes. Lan et al [17] carried out numerical and theoretical studies on static strength of internally ring-stiffened CHS DT-joints subjected to brace axial compression or tension, and proposed equations for predicting the capacity of the DT-joints.…”
Section: Introductionmentioning
confidence: 99%